2010
DOI: 10.26719/2010.16.3.266
|View full text |Cite
|
Sign up to set email alerts
|

Changes in tobacco use among 13-15-year-olds between 1999 and 2007: findings from the Eastern Mediterranean Region

Abstract: This report focuses on change over time in tobacco use among adolescents in countries included in the Eastern Mediterranean Region (EMR) of the World Health Organization. The Global Youth Tobacco Survey (GYTS) was conducted in each site at least twice between 1999 and 2007. Results indicate that for students aged 13-15 years tobacco use is a major public health problem. Increase in the use of water pipe, the likely initiation of smoking by never smokers, and a potential increase in tobacco use among young girl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 3 publications
1
28
1
1
Order By: Relevance
“…We can locate very few studies that target this exact age group of Jordanian youth in order to compare our findings. (9,13). A recent study of 7th grade students (a younger cohort) in Irbid, Jordan also reported a lower prevalence of current smoking (7) compared with our study.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…We can locate very few studies that target this exact age group of Jordanian youth in order to compare our findings. (9,13). A recent study of 7th grade students (a younger cohort) in Irbid, Jordan also reported a lower prevalence of current smoking (7) compared with our study.…”
Section: Discussioncontrasting
confidence: 51%
“…In Egypt, the GYTS revealed that 4% of 13-15 year olds were current smokers in 2005 (13), a considerably lower figure than the 19.8% reported in Jordan by the same study. In the latest GYTS survey, Jordan ranked 4th from among 15 countries, (after Palestine West Bank, Syrian Arab Republic and Kuwait), with regard to the prevalence of current smoking (13).…”
Section: Discussionmentioning
confidence: 99%
“…23 Doğu Akdeniz ülkelerinde ergenlik çağındaki bazı çocukla-rın nargile içmesine izin verildiği, bazı ailelerin yemeklerden sonra nargileyi paylaştığı saptanmıştır. 32 Nargile ve açık tütün kullanımı, uyuşturucu almak gibi eğlence anlayışları-nın taşıdığı tehlikelerle karşılaştırıldığında güvenli bir sosyal aktivite aracı olarak lanse edilebilmektedir. Araştırma grubunda nargilenin kültürel yönünden hoşlananların çok olması, bu gibi kültürel ve sosyal etmenlere bağlanabilir.…”
Section: Discussionunclassified
“…Findings from the GYTS, that involved more than 90,000 Arab children (13-15 years old), indicated that waterpipe smoking surpassed cigarette smoking among youth (El-Awa et al, 2010;Warren et al, 2006). Jordan for instance, is one of the EMR countries that has higher prevalence of waterpipe smoking compared to cigarettes.…”
Section: Introductionmentioning
confidence: 99%
“…Arab children (13-15 years old), the prevalence of waterpipe smoking surpassed that for cigarettes among youth (El-Awa et al, 2010;Warren et al, 2006). Nevertheless, most national and international tobacco control strategies are not specifically addressing this method of tobacco use (Maziak, 2011).…”
Section: Introductionmentioning
confidence: 99%